2013
DOI: 10.4103/0970-9185.119172
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of levobupivacaine in regional anesthesia: A systematic review

Abstract: The quest for searching newer and safer anesthetic agents has always been one of the primary needs in anesthesiology practice. Levobupivacaine, the pure S (−)-enantiomer of bupivacaine, has strongly emerged as a safer alternative for regional anesthesia than its racemic sibling, bupivacaine. Levobupivacaine has been found to be equally efficacious as bupivacaine, but with a superior pharmacokinetic profile. Clinically, levobupivacaine has been observed to be well-tolerated in regional anesthesia techniques bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(91 citation statements)
references
References 59 publications
3
80
0
8
Order By: Relevance
“…Our observation is similar to the results of Bajwa SS et al [6] , who in their study of Clinical profile of levobupivacaine in regional anaesthesia found that the time to onset of sensory and maximum motor block as well as the duration of analgesia is slightly longer with intrathecal levobupivacaine as compared to bupivacaine in caesarean section. In 2014, Del-Rio Vellosilo et al .…”
Section: Resultssupporting
confidence: 81%
“…Our observation is similar to the results of Bajwa SS et al [6] , who in their study of Clinical profile of levobupivacaine in regional anaesthesia found that the time to onset of sensory and maximum motor block as well as the duration of analgesia is slightly longer with intrathecal levobupivacaine as compared to bupivacaine in caesarean section. In 2014, Del-Rio Vellosilo et al .…”
Section: Resultssupporting
confidence: 81%
“…Levobupivacaine has been found to be equally efficacious as bupivacaine, but with a superior pharmacokinetic profile and less cardiac and neurological toxic adverse effects. 3,4 Various intrathecal adjuvants are being used with local anaesthetics for prolongation of the duration and quality of block. However, there is limited benefit either due to the adverse effects or unreliable post-operative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…This can be evidenced by the fact that equal doses of both Levobupivacaine and Bupivacaine provide same duration of analgesia (4-6hr) but with a better clinical safety with Levobupivacaine. 16 However, the median duration of analgesia when 0.5% Ropivacaine was injected for surgery was 1.7-4.2 hours. 22 This can be further substantiated by studies conducted by Peduto et al 8 Kara et al 21 Senard et al 23 Rao et al 10 Brown et al 24 Morrison et al 18 where the duration of analgesia produced by Ropivacaine is much lesser in comparison to Levobupivacaine.…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…16 The quality of pain relief from low-dose epidural infusions of plain local anaesthetic consistently benefits from the addition of adjuvants such as opioids (Hubler et al, 2001, 25 Senard et al 2002 23 ) or alpha-2 adrenoceptor agonists. Potential dose-sparing benefits are more obvious for local anaesthetic side effects (hypotension and motor block) than for opioid-related side effects.…”
Section: Postoperative Analgesiamentioning
confidence: 99%